Perencanaan Desain Tapak Jasa Lingkungan Wisata Alam Di Hutan Lindung Gunung Mahawu - Sabintoe, Bernat; Walangitan, Hengki D.; Pakasi, Sandra (Sam Ratulangi University, 2023)
The main objective of this study is to develop a site design for planning the development and management of natural tourism environmental services that are harmonious and harmonious with the natural environmental conditions in the Mount Mahawu Protection Forest by describing the potential, potential distribution and site analysis of each potential natural tourist attraction object. This research began in March to May 2023. The data used in this study were secondary data and primary data. Survey methods namely observation and inventory are used to obtain primary data in the form of biophysical data on research locations, types of potential natural tourist attraction objects as well as information on flora and fauna obtained at potential ODTW points determined by purposive sampling. Secondary data was obtained from a literature study as well as data from related institutions, namely the Forest Management Unit V of the Regional Forestry Service of North Sulawesi Province. The results showed that there were 6 forms of Land Mapping Unit (LMU) and 7 Land Utilization Types (LUT). The level of feasibility of developing ODTW potential consists of low to high categories. The high potential category is in LMU V and VI. LMU II is in the medium category class, LMU I, III and IV are in the medium and low categories. Alternatives to developing management space consist of business space covering an area of 522.663 Ha and public space of 53.265 Ha or 9.25% of the total site area by considering ecological, policy, technical and socio-cultural aspects.